Inspiring Through Interaction: The Impact of Teachers' Verbal and Non-Verbal Communication in EFL Classes - Ruswandi, Riki; Arief, Muhamad; Novitasari (VELES Voices of English Language Education Society, 2024)
Effective verbal communication, including clear explanations and constructive feedback, ensures that students comprehend the material and feel supported. Nonverbal communication, such as gestures, facial expressions, and eye contact, significantly contributes to sustaining student engagement and motivation. This research examines teachers' various verbal and nonverbal communication techniques in English as a Foreign Language (EFL) classes and explores their impact on student motivation. The study involved two teachers and 57 students from senior high schools in Indonesia, employing a phenomenological qualitative approach. Data collection methods included observation checklists, interviews, and questionnaires. The analysis revealed that teachers utilized seven distinct verbal communication methods—lecturing, questioning, giving directions, providing praise and encouragement, and offering feedback—and seven nonverbal methods, including eye contact, hand movements, physical proximity, facial expressions, physical appearance, and chronemics (the strategic use of time). Among these, students rated suggestions, praise, and encouragement as the most motivating verbal interactions, while eye contact emerged as the most influential nonverbal factor. These findings underscore the need for targeted teacher training in these communication strategies to foster a more engaging and motivating learning environment, thereby enhancing student learning outcomes in Indonesian EFL contexts.